Associação entre a ansiedade e depressão e o líquen plano bucal - Martins, Joana Dourado (2014)
Introduction: Oral lichen planus is a chronic inflammatory disease, potentially malignant. Objective: To evaluate the association between psychological states (anxiety and depression) and oral lichen planus. Methods: In a first study, a systematic review by consulting the electronic databases was performed (PubMed, Science Direct and LILACS) in the period between October 2013 and January 2014, using a predefined protocol. A critical evaluation of the literature was conducted in three stages by two reviewers independently, strictly observing the established inclusion and exclusion criteria. The quality of the articles was assessed based on the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE). For the second study, in a case-control model were established two groups, the cases group composed of individuals with a clinical diagnosis / histopathological of LPB and the control group, made up of individuals obtained the same reference population of cases, no history oral lichen planus, admitted at random and matched by sex and age in those cases. Both groups were subjected to thorough clinical examination of the oral cavity, interview and psychometric tests (Anxiety Inventory and Beck Depression). Data were statistically analyzed using the Data Analysis and Statiscal Software (StataSE- StataCorp LP) version 10. Results: For the systematic review, seven articles were selected at the end of the analysis and in four of them were observed a significant association between psychological changes and the development of oral lichen planus. The analysis of the quality of the articles through the STROBE showed an average of 11.3 items included, with a standard deviation of 2.2. For the case-control, there was an association between psychological disorders and OLP (p <0.001), and the crude OR of the principal association 5.06 (95% CI: [2.02 to 12.08]), while in subgroup analysis, the multivariate model adjusted for occupation and indicated an adjusted OR of 3.67 (95% CI: [1.05 to 3.46]), also statistically significant. Conclusion: Based on the results obtained in the studies, safeguarding the necessary limitations of the proposed models, there was an association between OLP and the presence of anxiety and depression.